PESANTREN : ASAL-USUL DAN PERTUMBUHAN KELEMBAGAAN - Normuslim, Normuslim (LP2M IAIN Palangka Raya, 2013)
Pesantren is Islamic institution of formal education first and oldest in Indonesia, which still exists and continues to grow today in terms of both quantity and quality. Pesantren is typical of Indonesian Islamic formal educational institution, because in the Islamic world cannot be found anywhere other than the Indonesian educational institution called the pesantren or Islamic boarding schools. However, there are two opinions that develop on the origin of boarding, the first opinion states that the origin of the word and the education system is derived from the Hindu-Buddhist, the second opinion states that although it is recognized that the term boarding is not at all found in the terminology of Islam (Arabic), however, the model or the system of education comes from Islam itself.In institutional, pesantren growth since before independence until today many experienced tides. In the Dutch colonial era to the independence of many boarding schools suffered a setback due to government policies that are less profitable existence as an educational institution of Islamic boarding schools. Today, boarding back up to adjuste the system and the curriculum with the development of times, science and technology, hence boarding is quite appealing to some Muslim communities not only from within the country, but also abroad.